The Feasibility of Adducing to the Islamic Legal Maxim ”الحرام لا یحرّم الحلال“ the Next Prohibited Doesn’t Make the Preceding Permitted Be Unlawful Relating to Zina in Marriage Book with Compliance with Article 1055 of Civil Code of Iran - Mahdi Moazami Goudarzi; Sayyed Muhammad Hasan Mousavi Khorasani; Meytham Khazaei; Hojjat Pouladin (آموزه‌‌های فقه مدني, 2021)
The Islamic legal maxim ”الحرام لا یحرّم الحلال“ the prohibited (Arabic: حرام unlawful) does not get the preceding permitted (Arabic: حلال lawful) is of the Islamic legal maxims which is on the basis of Particular injunction or text (nass) is related to the marriage book which has no fault from the point of its sanad (the chains of the narrator) but from the point of the content, many discussions have been propounded about the terms ”حلال“ and ”حرام“ (lawful and unlawful) according to the Islamic law. Majority of Imamiyah jurists believe that ”حلال“ lawful in the maxim includes both actual halal and potential halal. Also the well-known jurists believe that ”حرام“ unlawful which is indicated in the maxim are five instances: adultery, male homosexuality, illegal touching, unlawful gazing and relations. Since the opinions of Islamic jurists in the compliance or non-compliance of the maxim with adultery (Arabic: زنا Zinā) are dissimilar. Therefore, the present paper with descriptive-analytic method has studied the mentioned issues and has followed this outcome that if the act of Zina occurs after the lawful marriage contract the act of adulterer and adulteress and also a married woman who commits zina Even she insists on it for this determined maxim and the other proofs has no effect on the lawful contract (Arabic: عقد aqd) of the married woman (having sexual relations or not having with). Also is zina is before the marriage contract and the case of zina being potential halal this maxim is effective. This is the outcome which is resulted from Article 1055 of the civil code of Iran.